Pemberdayaan Masyarakat Hukum Adat Dalam Pelaksanaan Program Desa Wisata Mangrove - angga, La Ode; Labetubun, Muchtar Anshary Hamid (AIWADTHU: Jurnal Pengabdian Hukum, 2023)
Introduction: Mangrove forests are indispensable for coastal communities, because they can protect their areas when the water is high tide and very strong winds. Tourism with management by residents always prioritizes a bottom-up approach, and sustainable tourism always prioritizes a top-down approach.Purposes of Devotion: After participating in mentoring activities, the preparation / empowerment of indigenous peoples in the implementation of the Mangrove Tourism Village Program in Ahoi Rat Kecamatam Kei Kecil Timur, Southeast Maluku Regency. Method of Devotion: The implementation methods used in the realization of the Excellent Prosuk Development program are counseling, training and mentoring.Results of the Devotion: The service with the title Empowerment of Indigenous Peoples in the Implementation of the Mangrove Tourism Village Program in Ahoi Rat Kecamatam Kei Kecil Timur, Maluku Regency, was carried out in Ahoi Rat Kecamatam Kei Kecil Timur, Maluku Regency. Implemented with stages: 1. Planning Stages of the Mangrove Tourism Village Program in Ohoi Rat, Kei Kecil District, 2. Phase of implementation of the Mangrove Tourism Village Program in Ohoi Rat, Kei Kecil District and 3. Stages of Mangrove Tourism Village Supervision Planning Mangrove Tourism Village Program in Ohoi Rat, Kei Kecil District.